METHODS OF PEDAGOGICAL TECHNOLOGY - Rukhan, Jalik (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2022)
Efficiency of the educational process directly depends not only on the teacher’s knowledge of the material presented, but also on the ability to present this information. Pedagogical technology is the most important component of the teacher’s skill, which allows him to develop and improve in his profession. To understand the whole essence of this concept, it is necessary to consider it in more detail.